Relationship Transpiration Ability with Growth Dimension of Seedling Acacia decurens Inoculated with Glomus etunicatum and Gigaspora margarita HUBUNGAN KEMAMPUAN TRANSPIRASI DENGAN DIMENSI TUMBUH BIBIT TANAMAN Acacia decurrens TERKOLONISASI Glomus etunica - Arif Budi Setiawan; Sri Wilarso Budi R.; Cahyo Wibowo (Jurnal Silvikultur Tropika, 2015)
Transpiration plays very important role in ensuring good plant metabolism. However, techniques/methods used for its assessment are difficult and also quite demanding in terms of resources and technical know-how. Again, the results from transpiration measurements are not applicable to different samples and locations. Therefore it is necessary to study the relationship between transpiration ability with growth dimension of seedlings for predicting transpiration ability by a simple method. The research design was the completely randomized design with mycorrhizae arbuscular inoculants. This study used inoculants from silviculture laboratory identified as Glomus etunicatum (M1) and Gigaspora margarita (M2). Regression model analysis was used to determine the relationship between transpiration ability with growth dimension of Acacia decurrens seedling. There was a positive effect of mycorrhizae symbiosis which increased the transpiration ability with a strong relation for increasing seedling growth dimension. Transpiration ability is superior in G. etunicatum of 0.002863 mol m-2 s-1. The transpiration ability in control and G. etunicatum could be predicted with regression equation of R2 >70%, but in M2 intervention the model could not be predicted it was because of multi-colonization between the independent variable.Key words: Acacia decurrens, Gigaspora margarita, Glomus etunicatum, Regression, Transpiration